Mediateka - digitalizacija in trajno hranjenje zvokovnih vsebin RTV Slovenija - Kosi, Bojan (Knjižnica, 2011)
RTV Slovenia's archives contain large amounts of audio and video materials, various documents and music scores, and most of them are still in the analogue format. Widespread digitization has revolutionized the processes and ways of creating content in the digital format, recorded on different media. Such records also require new ways of preservation. In the article the development and structure of the Mediateque department at RTV Slovenia is presented. Also on overview to the preservation model of audio content is given. Due to rapid technological changes the audio content was the most critical and the first to be digitized. The intensive work in Mediatheque began in 2008 and after two years Radio Slovenia has developed modern system of permanent storage of audio content. Radio Slovenia's Digital Archive meets all the standards and regulations applicable to modern archival systems. In the article the application of Mediarc software is also presented, which as it could be used for digitizing and permanent storage of TV Slovenia's video archives.
Keywords: mediateka; archival science; arhivistika; digitalni arhivi; digitization; digitalizacija; zvokovne vsebine; Radiotelevizija Slovenija; RTV Slovenija; Radio Slovenija